Гностична парадигма та її типологічні паралелі з філософією Індії - Чикарькова, М.Ю. (Культура народов Причерноморья, 2013)
Витоки гностицизму та його типологічні паралелі з давньоіндійською філософією мало
беруться до уваги, хоча саме в гностицизмі було сформульовано відому ідею, співзвучну деяким
давньоіндійським (особливо ж буддійським) мислителям: світ побудовано «погано». Гностицизм став
альтернативою біблійній концепції, ґрунтом для спроб дискредитувати ідею Творця та висунути
завдання активної «переробки» світу - від міркувань розенкрейцерів до вчення марксистів і взагалі
«секулярних релігій» Новітнього часу. Истоки гностицизма и его типологические параллели с древнеиндийской философией мало
принимаются во внимание, хотя именно в гностицизме была сформулирована известная идея, созвучная
некоторым древнеиндийским (особенно буддийским) мыслителям: мир создан «плохо». Гностицизм стал
альтернативой библейской концепции, почвой для попыток дискредитировать идею Творца и
выдвинуть задачу активной «переработки» мира - от соображений розенкрейцеров до учения
марксистов и вообще «секулярных религий» Нового времени. Studies of Gnosticism in philosophical perspective are not so much. In the history of Philosophy
Gnosticism usually is treated as purely local product of Hellenists thought. But Gnostic’s teaching has, it seems,
typological parallels contribute Hellenists Egypt. In particular, gnostic conception of all creation is like Indian
Understanding of matter as Maya - «bubbles», ghosts. Even more deeply are parallels between Gnosticism and
Buddhism which started to realize by europian Philosophy only in XX century. And solely this compared was
opened especially in accordance with Mahayana Buddhism: to enter in Pleroma / Nirvana can only «enlighten
person» although idea of Salvation in Buddhism and Gnosticism is differently). But typological parallels with
Gnosticism and ancient Indian philosophy little taken into account, although in Gnosticism has been formed
famous Idea consonant some Hindu (especially Buddhist) thinkers: world is creatures too sick that may be
transformed. Gnosticism became an alternative to the biblical conception, a fertile ground for attempts to
discredit the Creator's idea and put forward the task of active recycling of the world - from considerations of the
Rosicrucians to the teachings of the Marxists and all «secular religion» the New time.